Independent origin and global distribution of distinct plasmodium vivax duffy binding protein gene duplications - Hostetler, J; Lo, E; Kanjee, U; Amaratunga, C; Suon, S; Sreng, S; Mao, S; Yewhalaw, D; Mascarenhas, A; Kwiatkowski, D; Ferreira, M; Rathod, P; et al. (Public Library of Science, 2016)
BACKGROUND:Plasmodium vivax causes the majority of malaria episodes outside Africa, but remains a relatively understudied pathogen. The pathology of P. vivax infection depends critically on the parasite's ability to recognize and invade human erythrocytes. This invasion process involves an interaction between P. vivax Duffy Binding Protein (PvDBP) in merozoites and the Duffy antigen receptor for chemokines (DARC) on the erythrocyte surface. Whole-genome sequencing of clinical isolates recently established that some P. vivax genomes contain two copies of the PvDBP gene. The frequency of this duplication is particularly high in Madagascar, where there is also evidence for P. vivax infection in DARC-negative individuals. The functional significance and global prevalence of this duplication, and whether there are other copy number variations at the PvDBP locus, is unknown. METHODOLOGY/PRINCIPAL FINDINGS:Using whole-genome sequencing and PCR to study the PvDBP locus in P. vivax clinical isolates, we found that PvDBP duplication is widespread in Cambodia. The boundaries of the Cambodian PvDBP duplication differ from those previously identified in Madagascar, meaning that current molecular assays were unable to detect it. The Cambodian PvDBP duplication did not associate with parasite density or DARC genotype, and ranged in prevalence from 20% to 38% over four annual transmission seasons in Cambodia. This duplication was also present in P. vivax isolates from Brazil and Ethiopia, but not India. CONCLUSIONS/SIGNIFICANCE:PvDBP duplications are much more widespread and complex than previously thought, and at least two distinct duplications are circulating globally. The same duplication boundaries were identified in parasites from three continents, and were found at high prevalence in human populations where DARC-negativity is essentially absent. It is therefore unlikely that PvDBP duplication is associated with infection of DARC-negative individuals, but functional tests will be required to confirm this hypothesis.